Characterisation of meta-analytical functional connectivity in progressive supranuclear palsy. Issue 4 (April 2018) - Yu, F.; Barron, D.S.; Tantiwongkosi, B.; Fox, M.; Fox, P.
Abstract : Aim: To characterise the meta-analytical functional connectivity patterns in progressive supranuclear palsy (PSP) and compare them to idiopathic Parkinson's disease (IPD). Materials and methods: It was previously reported that PSP and IPD showed distinct regions of brain atrophy based on voxel-based morphometry (VBM) meta-analysis. Using these regions as seeds, healthy control data were referenced to create and statistically compare meta-analytical functional connectivity maps of PSP and IPD. Results: Some overlap was noted between the two diseases, including within the thalamus, striatum, and prefrontal cortex; however, the PSP seeds demonstrated more extensive functional co-activity throughout the brain, particularly within the midbrain, precentral gyrus, parietal cortex, basal ganglia, and cerebellum. Conclusion: These findings may help guide future longitudinal studies in the development of new functional imaging biomarkers for diagnosis and assessing treatment response. Highlights: Meta-analytic connectivity modeling of PSP and IPD atrophy was performed. There was overlap in meta-analytic co-activity within thalamus, striatum, and frontal cortex. PSP demonstrated more extensive and posteriorly distributed co-activations. These correlate with recent fMRI studies, and may help to guide future prospective neuroimaging research.